Scouting for Huanglongbing (HLB; Citrus Greening) - Jamie D. Burrow; Stephen H. Futch; Tripti Vashisth (EDIS, 2019)
This 5-page publication is a minor revision that describes the following: 1) symptoms of HLB and how to distinguish these symptoms from those of other diseases/disorders; 2) when to scout; 3) different methods of scouting; and 4) what to do when an HLB-affected tree is identified. Written by Jamie D. Burrow, Stephen H. Futch, and Tripti Vashisth, and published by the Horticultural Sciences Department, December 2019.